2007
DOI: 10.3171/jns.2007.106.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan: a potential new chemotherapeutic agent for atypical or malignant meningiomas

Abstract: Irinotecan demonstrated growth-inhibitory effects in meningiomas both in vitro and in vivo. Irinotecan was much more effective against the malignant meningioma cell line than against primary meningioma cultures. Therefore, this drug may have an important therapeutic role in the treatment of atypical or malignant meningiomas and should be evaluated further for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Other newer agents, such as irinotecan and temozolomide, were deemed to have the potential to prevent recurrence, but failed in recent studies. [6][7][8]10 Therefore, at this time, the use of these agents should be reserved for patients who have documented recurrence and are not surgical candidates, and whose lesion is unresponsive to radiation. Based on the findings in this study, surgery is an effective therapy, even for recurrent tumors, and should be considered an option for all patients able to undergo an operation.…”
Section: Discussionmentioning
confidence: 99%
“…Other newer agents, such as irinotecan and temozolomide, were deemed to have the potential to prevent recurrence, but failed in recent studies. [6][7][8]10 Therefore, at this time, the use of these agents should be reserved for patients who have documented recurrence and are not surgical candidates, and whose lesion is unresponsive to radiation. Based on the findings in this study, surgery is an effective therapy, even for recurrent tumors, and should be considered an option for all patients able to undergo an operation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Currently, there are no chemotherapeutic regimens that effectively treat meningiomas, but agents such as bevacizumab are being evaluated for the treatment of Grade II and III meningiomas. 4,10 Finally, hypofractionated radiosurgery delivery systems, such as the Gamma Knife Extend (Elekta Instruments AB) may expand the versatility of radiosurgical treatment and ultimately result in better outcomes for patients harboring Grade II and III meningiomas.…”
Section: The Role Of Radiosurgery For Who Grade II and Iii Meningiomasmentioning
confidence: 99%
“…The study of Chamberlain et al [69] on the contrary showed a limited efficacy. Contrasting results exist on the efficacy of irinotecan on preclinical studies [70].…”
Section: Chemotherapymentioning
confidence: 96%